EVOLUSI TEKTONIK BERDASARKAN ANALISIS DATA KEKAR DAERAH BINUANG DAN SEKITARNYA, KECAMATAN BINUANG, KABUPATEN TAPIN, PROVINSI KALIMANTAN SELATAN - Yusuf, Andi Supian; -, Ismawan; Helmi, Faisal (Bulletin of Scientific Contribution, 2014)
Research area administratively located in Binuang district, Tapin Regencies, South Kalimantan Province. Geographically located in coordinate 115° 3' 40,359" East Longitude until 115° 15' 49,871" East Longitude and 3° 1' 7,068" South Latitude 3° 16' 10,038" South Latitude. Based on its physiography aspect, the research area is part of Barito Basin. The object of these research area the geological structures which is focused on the measurement of the fractures on rocks which represents each present tectonic periods, which is used for determining force and the tectonic pattern in the research area. As seen from the field data, it is known that the geological structures available in the research area are anticline, sincline, fracture, sinistral wrench fault, and reverse fault. The tectonic evolution on the research area begins during rifting which continues since Pra-tersier until Eosen with NE-SW direction, resulting the reverse faults with the fault surface estimated to be NW-SE direction, during Pliosen period reactivation of older faults happened on research area. The tectonic process changed into compression with NW-SE direction.